2013
DOI: 10.1002/tect.20044
|View full text |Cite
|
Sign up to set email alerts
|

Thermochronometrically constrained anatomy and evolution of a Miocene extensional accommodation zone and tilt domain boundary: The southern Wassuk Range, Nevada

Abstract: [1] Apatite (AHe) and Zircon (ZHe) (U-Th)/He thermochronometric data from the southern Wassuk Range (WR) coupled with 40 Ar/ 39 Ar age data from the overlying tilted Tertiary section are used to constrain the thermal evolution of an extensional accommodation zone and tilt-domain boundary. AHe and ZHe data record two episodes of rapid cooling related to the tectonic exhumation of the WR fault block beginning at~15 and~4 Ma. Extension was accommodated through fault-block rotation and variably tilted the souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…2; Table 2). Our findings are supported by the work of Gorinsky et al (2013), who suggested that the fault near Mt. Grant has slipped at a higher vertical displacement rate than the Wassuk fault further north.…”
Section: Long-term Vertical Displacement Rates From Faceted Spur Analsupporting
confidence: 89%
See 1 more Smart Citation
“…2; Table 2). Our findings are supported by the work of Gorinsky et al (2013), who suggested that the fault near Mt. Grant has slipped at a higher vertical displacement rate than the Wassuk fault further north.…”
Section: Long-term Vertical Displacement Rates From Faceted Spur Analsupporting
confidence: 89%
“…Importantly, based on our analysis of long-term vertical displacement, with greater vertical displacement rates in the south relative to the north, we suggest that seismic risk should be slightly elevated proximal to the southern section of the fault relative to the northern section, consistent with seismic hazard maps generated by Petersen et al (2008) and recent structural and thermochronologic data that reveal the highest post-4Ma uplift rates in the Wassuk Range are associated with the Wassuk fault adjacent to Mt. Grant (Gorinsky et al, 2013).…”
Section: Temporal Variation Of Vertical Displacement Ratessupporting
confidence: 78%
“…For each of these scenarios we conducted analogous simulations but run with n = 2/3 and n = 5/3 and present those results in the Supplement. Although the transient response to both uniform rock uplift/base level fall and step changes in uplift rate or erodibility have been extensively researched (e.g., Baldwin et al, 2003;Bonnet and Crave, 2003;Grimaud et al, 2016;Howard, 1994;Rosenbloom and Anderson, 1994;Royden and Perron, 2013;Tucker and Whipple, 2002;Whipple and Tucker, 1999), we include these perturbations herein to provide comparisons between well-known transient responses and those induced by tilt or truncation. We hope that this comparison highlights the fact that many perturbations disrupt the collinearity of mainstems and tributaries and that examination of the relationship between mainstems and tributaries can facilitate reconstruction of tectonic histories.…”
Section: Modeling Fluvial Longitudinal Profile Response To Perturbationsmentioning
confidence: 99%
“…Previous studies have illustrated the expected transient response in bedrock rivers to step changes in uniform rock erodibility or uplift rate (Baldwin et al, 2003;Bonnet and Crave, 2003;Howard, 1994;Royden and Perron, 2013;Tucker and Whipple, 2002;Whipple and Tucker, 1999), sudden base-level fall or uniform pulses of rock uplift (Grimaud et al, 2016;Rosenbloom and Anderson, 1994;Whipple and Tucker, 1999), erosion through layered stratigraphy (Forte et al, 2016), and cyclic fluctuations in rock erodibility, base level, or uplift rate (Goren, 2016;Snyder et al, 2002). Kirby and Whipple (2001) predict that steady-state bedrock rivers adjusted to uplift gradients with the maximum uplift either at the channel head or the channel outlet will have increased and decreased concavities (rate of change of the river slope with distance downstream), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Moho temperatures were varied between 600 and 1100°C, and radiogenic heat production from 5 to 50°C Ma −1 . These broad ranges were chosen because these parameters are not well constrained for the SSR; however, they combine to yield upper crustal geothermal gradients of 20–55°C km −1 , bracketing Tertiary estimates for the Basin and Range [e.g., Foster and John , ; Stockli et al ., ; Gorynski et al ., ; Long et al ., ]. The combination of these thermal parameters with the strain history variables yields a prior distribution p ( T ), where T is the set of probability distributions for each variable t in T .…”
Section: Thermochronologic Modelingmentioning
confidence: 99%